Internationalization paths of Chinese firms: Evidences from an emerging economy - Zeng, Saixing; Shen, Qi; Tam, Chiming; Wan, Tianwei (Journal of Business Economics and Management, 2010)
In this paper, an empirical study is conducted to explore the paths of internationalization for Chinese manufacturing firms. Correspondence analysis was employed to examine the relationship between the internationalization paths and the firms’ form of ownership. It reveals that the internationalization paths of Chinese firms appear to be in a form of terrace structure, more firms adopting the rudimentary levels than the more matured courses of internalization. The findings indicate that Chinese firms are characterized by the relatively low levels of internationalization. Also the preferred destinations of going internationalization were identified for firms adopting outward foreign direct investments.Kinijos įmonių internacionalizavimo būdai: tam tikri augančios ekonomikos bruožai Santrauka. Straipsnyje pateiktas empirinis tyrimas, atliktas siekiant išsiaiškinti internacionalizavimo būdus Kinijos gamybos įmonėse. Norint ištirti ryšį tarp internacionalizavimo būdų ir įmonės nuosavybės formos, buvo pritaikyta atitikties analizė. Ji parodė, kad internacionalizavimo būdai Kinijos įmonėse yra pylimo formos, t. y. dauguma įmonių diegia pradinio, be ne brandesnio lygmens internacionalizavimo būdą. Atskleista, kad Kinijos įmonėse internacionalizavimo lygis yra gana žemas. Nustatytas pageidautinas internacionalizavimo tikslas – išorinių tiesioginių užsienio investicijų naudojimas.Reikšminiai žodžiai: internacionalizavimo, internacionalizavimo būdai, išorinės tiesioginės užsienio investicijos, auganti ekonomika, Kinija.First Published Online: 09 Jun 2011